Spectrophotometric determination of meloxicam in pharmaceutical formulations - Donchenko, A. O.; Vasyuk, S. O.; Донченко, Анастасія Олександрівна; Васюк, Світлана Олександрівна (My University, 2022)
Inflammation is a complex local vascular-mesenchymal reaction to tissue damage caused by various agents. This reaction is aimed at destroying the agent that caused the damage and repairing the damaged tissue [1].